(untitled) - Maffei, Ken ([S.l.], 2003)
This courseware module introduces you to MAXScript, the scripting language built into 3ds max. This module covers the creation of objects with MAXScript, arrays, collections, control structures, the construction of UI elements, creation of parametric objects, and a variety of additional topics
Keywords: Computer software,Programming languages (Electronic computer),Phần mềm máy vi tính; Ngôn ngữ lập trình